Yoga tradition - "Feuerstein, Georg" (New Delhi, 2002)
From the foremost living authority on Yoga comes the most comprehensive and reliable treatment of the subject available today. This is a work of impeccable scholarship by a person who has dedicated his life to the understanding and practice of yoga. The book offers a complete overview of every Yogic tradition, from the familiar to the lesser-known forms. It also covers all aspects of Hindu, Buddhist and Jaina Yoga, including history, philosophy, literature, psychology and practice. In addition, included are translations of twenty Yoga treatises and the first translation of the Goraksha Paddhati.
Keywords: Yoga